Distinct Hypothalamic Paraventricular Nucleus Inputs to the Cingulate Cortex and Paraventricular Thalamic Nucleus Modulate Anxiety and Arousal - Liu, Ying; Rao, Bo; Li, Shuang; Zheng, Ning; Wang, Jie; Bi, Linlin; Xu, Haibo (Frontiers in Pharmacology, 2022)
Insomnia and anxiety are two common clinical diseases that threaten people’s physical and mental health. Insomnia and anxiety may share some similar underlying neural circuit mechanisms in the brain. In this study, we combine techniques including chemo-fMRI, optogenetics, and chemogenetics to reveal that the glutamatergic neurons of the paraventricular hypothalamic nucleus (PVN) regulate both anxiety and arousal through two different downstream neural circuits. Optogenetic activation of the PVN-cingulate cortex (Cg) neural circuit triggers anxiety-like behaviors in mice without affecting the wakefulness, while optogenetic activation of the PVN-paraventricular thalamic nucleus (PVT) neural circuit promotes wakefulness in mice without affecting anxiety-like behaviors. Our research reveals that PVN is a key brain area for controlling anxiety and arousal behaviors. We also provide a neurological explanation for anxiety disorder and insomnia which may offer guidance for treatments including drugs or transcranial magnetic stimulation for the patients.